Effects of maternity on labor outcomes and employment quality for women in Chile - Juan Pedro Eberhard; Javier Fernandez; Catalina Lauer (Journal of Applied Economics, 2023)
Parenthood have a significant impact on engagement in the labor force. Parents may decide to look for jobs with specific characteristics, and in some cases, they may decide to not participate in the labor market. Using survey data from Chile, we use a propensity score matching estimation to compare various labor outcomes of women and men with and without children. We found that maternity has an impact on several dimensions of labor engagement. To study how these multidimensional effects are compounded at the individual level, we use a quality of employment (QoE) index to estimate the drop in job quality post-childbirth. We found a drop in quality only for mothers. Moreover, for less educated women, the drop in QoE is equivalent to no longer being hired under contract. For single mothers, the drop is equivalent to a reduction in wages that would make the family fall below the poverty line.
Keywords: 330; child penalties; Gender differences; job quality